Fifty years of animal health at The Wildfowl & Wetlands Trust - Brown, Martin (Wildfowl, 1996)
The study of wildfowl disease and mortality was in its infancy when, in 1946, Peter Scott founded the Severn Wildfowl Trust at Slimbridge. The largest collection of captive wildfowl in the world was not to be without significant health problems, since the maintenance of high densities of birds on the same area for 50 years was a sure recipe for a host of infectious and parasitic disease outbreaks. In the United States, studies into large scale mortality of wild migratory waterfowl had been undertaken as early as 1920, and the importance of botulism and avian cholera, with their ability to cause mass mortality, had been recognised. In Europe, however, little was known of the disease status of captive and migratory waterfowl; this was a subject to which WWT would make a significant contribution during the next five decades.